The effect of virtual avatar experience on body image discrepancy, body satisfaction and weight regulation intention - Juyeon Park (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2018)
This experimental study aimed to investigate the effect of having a virtual avatar experience on health outcomes in the context of body image and weight regulation. Ninety-three U.S. non-clinical participants (51 men and 42 women) were recruited, who were 18 years and older and had no history of chronic health problems or mental illnesses. Each experiment consisted of the three data collection phases, including the pre-experiment survey, an experience session of a virtual self-avatar, and the post-experiment survey. For the development of the virtual avatar protocol, this study employed 3D body scanning to create a participant’s virtual body model based on accurate anthropometric data, to simulate a virtual avatar closely matched with the participant’s actual physique. Overall, the data indicated an increase in perceived body image discrepancy and a decrease in body satisfaction after participating in a virtual avatar session, and those who showed higher body dissatisfaction exhibited a stronger intention regulated for weight control. Specifically in gender, the statistical results were generally intensified in the female group, but the male group showed a stronger intention to be involved in exercising after virtual avatar experience. The insights gained from this study suggested future directions for research and program development, and urged that practical applications of the virtual avatar approach must be implemented with caution when it uses clinical samples, because its risk-benefit assessment has not been sufficiently investigated yet.